Magnetocardiography in the Evaluation of Sudden Cardiac Death Risk: A Systematic Review - Thomas Lachlan; Hejie He; Kengo Kusano; Takeshi Aiba; Donatella Brisinda; Riccardo Fenici; Faizel Osman (Annals of Noninvasive Electrocardiology)
ABSTRACT Sudden cardiac death (SCD) is responsible for 15%–20% of deaths globally/year, predominantly due to ventricular arrhythmias (VA) caused by vulnerable cardiac substrate. Identifying those at risk has proved difficult with several limitations of current methods. We evaluated the evidence for magnetocardiography (MCG) in predicting SCD events. We searched Embase/Medline databases for English language papers evaluating MCG in patients at risk of VA. A total of 119 papers were screened with 27 papers included for analysis (23 case–controlled, four cohort studies); study sizes varied (n = 12 to 158). Etiology was ischemic cardiomyopathy (ICM) in 22, dilated cardiomyopathy in 2, arrhythmogenic cardiomyopathy in 1 and mixed in 2. In patients with ICM there were consistent discriminatory features seen using time‐based and signal‐complexity measures that persisted when evaluating the independence of these parameters. Current flow analysis demonstrated promising discriminatory results in other etiologies. The features studied support the role of MCG in identifying substrate for VA, particularly in ICM.